THE TENDENCY OF USING MICRO TAKAFUL AMONG MICRO, SMALL AND MEDIUM ENTREPRENEURS AT PELEPAT ILIR, JAMBI, INDONESIA - Chusmita, Lina Ade; Razak, Azila Abdul; Muhammad, Fidlizan (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2019)
Micro takaful is one of the takaful product development strategies in developing the 'marginalized' economy of financial institutions. The objective of this study is to provide empirical evidence on financial inclusion as a factor of behavioral control in the Theory of Perceived Behavior (TPB) to analyze its influence with the tendency of micro, small and medium enterprises (MSME) entrepreneurs to the use of micro takaful. Data distributed via questionnaires to 372 respondents were analyzed using descriptive and structural equation modeling. The results of the study showed that there was a positive and significant effect between attitude and financial inclusion on the tendency of using micro takaful. On the contrary, subjective norm factors have no significant effect on the proposed model. The implications of the study indicate that financial inclusion is one of the most important policies to achieve sustainable development. In addition, takaful institutions and policy makers need to expand the supply of microfinance products, especially micro takaful scheme to MSME in Indonesia to ensure the protection and security of their businesses.